Microvariation and transfer in L2 and L3 acquisition. (July 2021) - Gabriele, Alison
This commentary discusses Westergaard's (2021) keynote article, which presents a comprehensive model of first language (L1), second language (L2), and third language (L3) acquisition. The commentary presents evidence from a previous study of L3 learners that provides support for Westergaard's property-by-property transfer proposal. The commentary highlights strengths of the proposal, such as its focus on microvariation, and also outlines open questions, such as whether the model can predict in advance whether specific properties will be easier or harder to acquire.